2020
DOI: 10.1038/s41612-020-00141-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced risk-based event attribution for heavy regional rainfall events

Abstract: Risk-based event attribution (EA) science involves probabilistically estimating alterations of the likelihoods of particular weather events, such as heat waves and heavy rainfall, owing to global warming, and has been considered as an effective approach with regard to climate change adaptation. However, risk-based EA for heavy rain events remains challenging because, unlike extreme temperature events, which often have a scale of thousands of kilometres, heavy rainfall occurrences depend on mesoscale rainfall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…It has been shown that some recent heavy rainfall events, as well as extreme temperature events were influenced by global warming (Imada et al 2020). There is an increasing need for better information regarding the temporal evolution of these extreme events from now to the end of this century, and on the timing of the emergence of the signal associated with any changes above the noise of natural variability (Hawkins et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some recent heavy rainfall events, as well as extreme temperature events were influenced by global warming (Imada et al 2020). There is an increasing need for better information regarding the temporal evolution of these extreme events from now to the end of this century, and on the timing of the emergence of the signal associated with any changes above the noise of natural variability (Hawkins et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to smaller signals in the lower level of warming in the recent past compared to future projections, many climate simulations with and without anthropogenic climate change since the industrial revolution have been compared to evaluate the effects of past anthropogenic effects on climate change. For example, the effects of human-induced global warming on past heavy precipitation events (Imada et al 2020;Li et al 2021) and mean and extreme streamflow (Gudmundsson et al 2021) have been investigated using large ensemble climate simulations. Despite evidence of a general increase in extreme precipitation events in the past (Hartmann et al 2013;Min et al 2011), the observed changes in flooding vary with catchment sizes or hydroclimatological characteristics (Do et al 2017;Sharma et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In July 2018 and July 2020, ARs passing through East Asia brought extreme rainfall and large social damages to the region (Araki et al., 2021; Hirockawa et al., 2020; Takemura et al., 2019; Tsuguti et al., 2019; Zhao et al., 2021). The higher frequency of AR‐induced natural disasters in recent years suggest a possible influence of ongoing global warming on the occurrence of extreme events (e.g., Imada et al., 2020; Kamae, Shiogama, et al., 2017; Kawase et al., 2020, 2019).…”
Section: Introductionmentioning
confidence: 99%